DETERMINAN PENGELOLAAN DANA DESA DI DESA KARANGASEM, KECAMATAN SAYUNG, DEMAK - Muhammad Nizar Ali; Devi Permatasari (Jurnal Gici Jurnal Keuangan dan Bisnis, 2025)
This study aims to analyze various factors influencing Village Fund management in Karangasem Village, Sayung District, Demak Regency. The Village Fund allocation is Rp 883,377,000 in 2024. The study used a quantitative approach with an analytical survey method for 75 respondents. The data was collected through a Likert-scale questionnaire and analyzed using multiple linear regression techniques. The results showed that accountability, supervision, and the competence of village officials positively and significantly influenced Village Fund management. Meanwhile, community participation and transparency did not have a significant effect. Simultaneously, all five variables influenced Village Fund management with a coefficient of determination of 79.2%. The researchers concluded that accountability and the competence of village officials were the dominant factors in effective Village Fund management